Treatment Interruption and Discontinuation of Hormone Therapy in Hormone Receptor-Positive Breast Cancer Patients - Mao, Daqin. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Susan Parsons.; Committee: Karen Freund, and Hong Chang.; Keyword: Health sciences.